EFFECTS OF FAC CHEMOTHERAPY ON ANTI MULLERIAN HORMONE IN PREMENOPAUSAL BREAST CARCINOMA - Winardi Budiwinata; Abdurahman Maman; Azhar Raden Yohana (Fakultas Kedokteran Universitas Lambung Mangkurat, 2022)
Abstrak: Breast cancer is the most common carcinoma in women in the world. Anti-Mullerian Hormone (AMH) is a hormone secreted by primary, secondary, and small antral ovarian follicles of <4mm. The chemotherapy regimen toxic to ovarian follicles is 5-fluorouracil-doxorubicin-cyclophosphamide (FAC). In Indonesia, there had been no study on the effect of FAC chemotherapy on AMH in premenopausal breast carcinoma patients. This study aims to determine the effect of FAC chemotherapy on AMH in premenopausal breast carcinoma patients. This study employed a prospective cohort study design. Inclusion criteria were breast carcinoma, premenopausal, and history of chemotherapy (-). Exclusion criteria were history of ovarian surgery, pelvic radiation, GnRH-agonist therapy, smoking for ≥10 years, obesity, and chemotherapy dropout. Subjects were examined for AMH before the 1st chemotherapy and after the 4th chemotherapy. Statistical test was done with Wilcoxon test, significant if p≤0.05. The average AMH level before FAC chemotherapy was 1.51±1.957; the average AMH level after the 4th FAC chemotherapy was 0.24±0.587. The result of the Wilcoxon test comparing AMH levels before and after 4th FAC chemotherapy was p<0.0001. FAC chemotherapy reduces AMH patients with premenopausal breast carcinoma.Keywords: Breast carcinoma, chemotherapy, AMH.